Causal Connectivity, Genidentity and the Ontology of Point-Eventism - Raźniak, Maciej (Logic and Logical Philosophy, 2025)
The concept of a causally connected set of point-events plays a crucial role in the point-eventistic definitions of a thing and a process formulated by Zdzisław Augustynek. Unfortunately, Augustynek’s approach to causal connectivity is open to a serious objection that has so far gone unnoticed, stemming from the way causal interactions are viewed in contemporary physics. This finding can hardly be considered favorable for an advocate of the ontology of point-eventism. The aim of this paper is, therefore, firstly, to discuss this objection in detail and, secondly, to share some ideas on how to deal with the problem.